Insights into the western tropical Pacific's role in late Pleistocene hydroclimate variability: 160ky Borneo stalagmite? 18O record - SA, Carolin; K, Cobb; JF, Adkins; B, Clark; S, Lejau,; S, Lejau,; J, Lynch-Stieglitz; J, Malang; AA, Tuen (American Geophysical Union, 2013)
The presence of multiple physical mechanisms at play throughout the Late Pleistocene makes it difficult to confidently attribute climate variability to particular forcings. The tropical Pacific's role in past climate change is especially ambiguous because most tropical records lack the resolution, length, and chronological control to completely resolve rapid variability - including abrupt climate change events, ice age terminations, and sea level shifts - against a background of orbital-scale variations. Stalagmites from Gunung Mulu, located in northern Borneo, allow for the construction of reproducible centennial-scale records of hydrologic variability that are precisely-dated and continuous throughout most of the late Pleistocene. Comparison of such records to other regional and global paleorecords as well as relevant simulations from numerical climate models provide valuable insights into the mechanisms responsible for western tropical Pacific hydroclimate variability on centennial to multi-millennial scales. Here we present a large compilation of overlapping U/Th-dated Gunung Mulu stalagmite delta18O records spanning the last 160ky. The composite records demonstrate the complex response of northern Borneo convection to both high-latitude and low-latitude forcings and external insolation. The ice-volume-corrected Borneo delta18O records show little correspondence between regional convective activity and either global sea level shifts (e.g. 1) or Sunda Shelf areal exposure. This result stands in marked contrast to a recently published Last Glacial Maximum (LGM) data-model synthesis that implicates sea level as a dominant driver of tropical Indo-Pacific hydroclimate variability (2). Alternatively, when precessional signals are not muted, the composite Borneo delta18O record varies in phase with equatorial fall insolation, suggesting that precessional forcing is the dominant cause of tropical western Pacific hydroclimate variability on orbital timescales. This is best illustrated across Termination II, when the oscillation of equatorial fall insolation is large and out of phase with ice sheet decay (e.g. 3). During this transition, Borneo stalagmite delta18O begins a shift to more negative delta18O values at 128.8 × 0.9 kybp, almost directly overlapping the equatorial fall insolation cycle. The muted response of tropical western Pacific hydrology to global temperature change and sea level rise relative to precessional insolation represents an important observational constraint on the sequence of climate feedbacks responsible for glacial terminations. 1. M. Medina-Elizalde. Earth Planet. Sci. Lett. 362, 310 (Jan, 2013). 2. P. N. DiNezio, J. E. Tierney. Nature Geoscience 6, 485 (Jun, 2013). 3. A. L. Thomas et al. Science 324, 1186 (May, 2009).